Pengetahuan, Kemampuan dan Pengalaman Terhadap Kinerja PADA UMKM Marshalia Embroidery - Yuyuk Liana; Rr. Widanarni Pudjiastuti (Bulletin of Management and Business, 2022)
The purpose of this study was to determine the effect of knowledge, ability and experience variables on employee performance, with a population of 40 respondents at the MSME Marshalia Emboidary Malang City. By distributing questions as data collection, and the results explain all these variables affect employee performance.